H.D.: Her life and work - McKay, B (1985)
This thesis argues that H.D.'s creativity originates in a flight from reality. Hilda Doolittle's adoption of her initials is interpreted as a sign of the writer's rejection of any identity located in the shared reality of the historical and the quotidian. From childhood her personality presented itself to her as a duality; detaching herself from the merely visible and material world, H. D. created an intense inner life which asserted itself in the dimension of artistic realization. It is argued that paradoxically the unevenness and discontinuity that characterize H.D.'s work derive from the same roots as her artistic originality and power: in her "split dual personality" which posited reality in the disembodied self. H.D. discovered in ancient Greece a metaphor and a direction for her own inner world. However her Imagist poems are not imitative but genuinely original: H.D. invented a new reality which she projected as a world devoid of all traces of human presence. H.D.'s subsequent shift of interest towards autobiographical prose is interpreted as a response to the threatened disintegration of her identity after World War I. The formlessness and repetition of much of H.D.'s prose is thus attributed to the exacerbation of the writer’s dichotomy of being. However, in some of her prose works H.D. succeeded in transfiguring the autobiographical material through the reinvention of reality in the image of her own subjectivity. Seeking new forms for her projection of the self, H.D. turned increasingly towards the occult which she understood as the science of the invisible dimension. She conflated with the occult her discoveries of the cinema as self-projection, and psychoanalysis as an instrument of knowledge of the inner being. It is argued that these interests exacerbated the solipsism inherent in H.D.'s rejection of external reality. With the exception of the war Trilogy, H.D.'s work becomes locked in private meanings which render it increasingly inaccessible to the reader. It is argued that after her mental breakdown in 1946, H.D. never recovered her vitality and originality as an artist. The space that this thesis devotes to the life of H.D. does not intend to justify her work by her life, but to signify that the literary message cannot be isolated from the circumstances in which the process of creation takes place. Thus H.D.'s flight from reality is not judged from an existential point of view as a diminution of being, since it is out of her "split dual personality" that H.D. emerges as a genuinely creative and original artist.